Espacio público como re-habilitador urbano para asentamientos informales de Cuenca Norte y Sur, Guararí, Heredia - Matarrita-Soto, Jean Carlo (Instituto Tecnológico de Costa Rica., 2019)
The purpose of this project is to tackle the subject of neighborhood improvement. This in the hopes of igniting a positive intervention in the communities of the northern and southern edges of the Guarari basin, located in Heredia, Costa Rica. This piece of work will function in the framework of overcoming challenges regarding the urban character of the region. The urban-architectural solution is possible due to the analysis of social systems within the communities. With participation of communal and external agents that affect the site, it is possible to create an action plan that is made up three elemental phases. The first phase consists of the clean up of the “Quebrada Tropical” basin. Proposing strategies to clean up the area and finding a solution to the contamination of the waterflow that has a negative impact on the surrounding context. Phase two proposes the improvement of urban infrastructure, especially in regards of pedestrian walkways. The objective is to enhance and increase access to this area. Lastly, phase three looks for the regeneration and increase of urban spaces to improve and develop communal activities in the neighborhood.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: Costa Rica, Heredia; Espacio urbano; Asentamientos informales; Rehabilitación urbana